2016
DOI: 10.1016/j.urolonc.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Frailty as a marker of adverse outcomes in patients with bladder cancer undergoing radical cystectomy

Abstract: Objective To investigate the modified frailty index (mFI) as a pre-operative predictor of post-operative complications following radical cystectomy in bladder cancer patients. Materials and Methods Patients undergoing radical cystectomy (RC) were identified from the National Surgical Quality Improvement Program (NSQIP) participant use files (2011-2013). The mFI was defined in prior studies with 11 variables based on mapping the Canadian Study of Health and Aging Frailty Index to NSQIP comorbidities and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 25 publications
4
87
1
Order By: Relevance
“…Frailty has been proposed as a more accurate predictor of postoperative complication than chronological age in various fields of surgery . Among the frailty indices proposed for perioperative risk stratification, the mFI has been identified as a stronger predictor of severe complications after RC than age and is useful for preoperative risk stratification, particularly in younger patients . In the present study, 20% of patients diagnosed with frailty showed equivalent complete response, protocol completion and survival rates after TeMT to those who were not diagnosed with frailty.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Frailty has been proposed as a more accurate predictor of postoperative complication than chronological age in various fields of surgery . Among the frailty indices proposed for perioperative risk stratification, the mFI has been identified as a stronger predictor of severe complications after RC than age and is useful for preoperative risk stratification, particularly in younger patients . In the present study, 20% of patients diagnosed with frailty showed equivalent complete response, protocol completion and survival rates after TeMT to those who were not diagnosed with frailty.…”
Section: Discussionmentioning
confidence: 54%
“…Frailty was further evaluated using the mFI, a simplified version of the original 70‐item Canadian Study of Health and Aging Frailty Index containing 11 preoperative variables, including functional health status and specific comorbidities of interest. This index was initially developed to predict complications in patients with colectomy; subsequently, it was shown to be a predictor of complications after RC . The mFI scores were retrospectively obtained from patients’ medical records at the time of protocol enrollment, and categorized into low (0 or 1) and high (>2) mFI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Chappidi et al [16] used the modified frailty index (mFI) to identify high-risk patients for 30-day complications and mortality. The mFI is an 11 variable score consisting of medical comorbidities, very similar in concept to the CCI, although including different medical conditions as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, bladder cancer disproportionately impacts an older population in whom medical comorbidities are common . Due to procedural complexity and necessary application within a comparatively fragile population, perioperative morbidity following radical cystectomy is high with complications reported in 28‐64% of patients . Length of stay following the procedure is often in the range of 10 days and highly dependent on occurrence of complications and return of bowel function .…”
Section: Radical Cystectomymentioning
confidence: 99%